2021
DOI: 10.31129/lumat.9.2.1401
|View full text |Cite
|
Sign up to set email alerts
|

Promoting STEAM learning in the early years: “Pequeños Científicos” Program

Abstract: Education in the early years is an excellent space for promoting integrated learning. The STEAM education model combines Science, Technology, Engineering, Arts and Mathematics holistically and has gained force globally, mostly in developed countries. However, in developing countries of Latin America, STEAM education programs are incipient and still unfamiliar to many early childhood and primary school educators. "Pequeños Científicos" is a pioneer educational program in Chile aimed at providing extracurricular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 27 publications
1
4
0
1
Order By: Relevance
“…It also helped to improve communication skills among students by asking colleagues for help when there was a glitch in a cooperative and friendly manner among them, distributing tasks and roles among them, and re-reading information in case the activity was not completed, which contributed to improving their corrective skills. This is what Cabello et al (2021) indicated in their study and on the development of the learner's own personality. Encourage learners to ask frequent questions and to ensure mastery and quality of work, as well as considering several options to complete the activity have contributed to the extent of monitoring the students' comprehension monitoring.…”
Section: Conclusion Twosupporting
confidence: 58%
“…It also helped to improve communication skills among students by asking colleagues for help when there was a glitch in a cooperative and friendly manner among them, distributing tasks and roles among them, and re-reading information in case the activity was not completed, which contributed to improving their corrective skills. This is what Cabello et al (2021) indicated in their study and on the development of the learner's own personality. Encourage learners to ask frequent questions and to ensure mastery and quality of work, as well as considering several options to complete the activity have contributed to the extent of monitoring the students' comprehension monitoring.…”
Section: Conclusion Twosupporting
confidence: 58%
“…These are crucial skills for tomorrow's political leaders, scientists, engineers, entrepreneurs, and teachers [15,61]. In addition to this, it has been shown both by this study and literature review [59,61,62] that STEAM can offer ways for extracurricular learning opportunities for all ages and educational levels. STEAM is a new way to promote students' creativity, collaboration, and collective being through transdisciplinary consciousness and conscience [42,61,63].…”
Section: Discussionmentioning
confidence: 73%
“…This aligns with the STEM approach that promotes students' active participation and integrates disciplines through project-based learning, enhancing academic and social skills [3][4][5][6]51]. Real-world problem-solving tasks further enrich the learning environment [22,36,37]. However, the practical application of these approaches still poses a significant challenge, underscoring the need to enhance teachers' technological competence [35,39,48].…”
Section: Discussionmentioning
confidence: 77%
“…The emphasis on developing teachers' digital competency is escalating, with a focus on gaining a deep understanding and skills to use technology to its fullest, particularly in delivering quality STEM education [22,36,37]. This urgent need goes beyond basic understanding, encouraging teachers to develop the capability to create, develop, and use innovative technological resources to enrich their pedagogical strategies [38,39].…”
Section: Initial Teacher Training In the Use Of Technologiesmentioning
confidence: 99%